Biometric Systems - Sarfraz, Muhammad (Biomedical Engineering, 2021)
Biometrics are used widely in various real-life applications today. There are a number of potential biometric applications that include different areas such as personal recognition, identification, verification, and others. It may be needed for safety, security, permission, banking, crime prevention, forensics, medical applications, communication, face finding, and others. This book is specifically dedicated to biometric research, applications, techniques, tools, and algorithms that originate from different fields such as image processing, computer vision, pattern recognition, signal processing, artificial intelligence, intelligent systems, and soft computing. The main objective of this book is to provide the international community with an effective platform in the area of people identity verification and authentication from physiological and behavioral aspects. This publication provides an effective platform for helping and guiding readers, professionals, researchers, academicians, engineers, scientists, and policy makers involved in the area of biometrics.